Effects of charge and size on the coadsorption of counterionic colloids in Gibbs monolayers - J. M. Gómez-Verdú; B. Martínez-Haya; A. Cuetos (Condensed Matter Physics, 2024)
This study uses a coarse-grained Monte Carlo algorithm to model and simulate the coadsorption of a binary mixture of counterionic colloids in Gibbs monolayers. These monolayers form at a idealized air-water interface, with one non-soluble species confined at the interface and the second one partially soluble in the aqueous phase. The investigation focuses on the effect of colloidal size and charge on the thermodynamics and microstructure of the monolayer. We find that the composition of the monolayer evolves non-trivially with surface coverage, depending on the balance of steric and electrostatic forces. When the electrostatic interactions are weak, the soluble species is expelled from the monolayer upon compression, yielding a phase behaviour particularly sensitive to the relative size of the soluble and non-soluble colloids. By contrast, strong electrostatic interactions favour the stabilization of the soluble particles in the monolayer and the formation of quasi-equimolar fluids, with only a weak dependence on particle size. The combination of these phenomena results in the formation of a number of two-dimensional mesoscopic arrangements in the monolayer, ranging from diluted gas-phase behaviour to domains of aggregates and percolates, and to incipient crystalline structures.